Indicator of Vibroacoustic Energy Propagation as a Selection Criterion of Design Solution - KLEKOT, Grzegorz (Archives of Acoustics, 2013)
Contemporary tools which help to design technical objects refer to the conclusions drawn from studyingthe changes of physical processes accompanying the exploitation, especially to vibroacoustic processes.The main problem is to define such vibroacoustic measures, where their changes would model the analyzedphysical phenomena in the best way. Basing on simple indicators which refer to occurring phenomena, it ispossible to obtain accurate solutions with a satisfactory reliance level without using complex computingtechniques needing detailed descriptors. According to the author, the indicators which are based onthe analysis of vibroacoustic energy propagation are very useful in solving engineering problems. Theseindicators are useful while diagnosing the condition of technical systems, identifying and minimizing thevibroacoustic risks. The possibilities of using such indicators in order to find design solution are illustratedby sample results of the research of the structures with vibroacoustic elements which reduce the noise ofrail vehicles by the rail vibration damping.